TOWARDS A SUSTAINABLE APPROACH OF CULTURAL TOURIST RESOURCES IN THE ORADEA METROPOLITAN AREA (OMA), ROMANIA - Corina-Florina TĂTAR; Ribana LINC; Marius I. STUPARIU; Marcu Simion STAȘAC; Iulian DINCĂ; Stelian NISTOR; Liviu BUCUR (Analele Universităţii din Oradea: Seria Geografie, 2021)
Metropolitan regions/areas are NUTS 3 regions or a combination of NUTS 3 regions which represent all agglomerations of at least 250,000 inhabitants (Eurostat, 2021). Oradea Metropolitan Area (NUTS3ID RO111) was established in 9th of May 2005 and has a total number of 251.570 inhabitants. The purpose of the association is to stimulate and support the growth and prosperity of the area, focused on the continuous increase of the quality of life. Besides the economic boost, OMA emerged from the need for space and leisure expressed by the core urbanites and although the periurban area is teeming with valuable cultural resources, the latter being the focus of the current study, they are little known by many of the Oradea residents. In this purpose the cultural attractions of the rural OMA were inventoried, analysed and stored in an online openaccess database so that tourists can enjoy them and entrepreneurs in tourism can use them as focal points for further tourist infrastructure development. The analysis highlighted the OMA periurban area with the highest cultural attractions’ potential based on the National Methodology regarding the evaluation of the tourist potential in the basic administrative-territorial units.